SYNTHESIS AND PROPERTIES OF DIAMINE(ISOPROPYLIDENEMALONATO) PLATINUM(II) - CRYSTAL-STRUCTURE OF O(CH2CH2)(2)C(CH2NH2)(2)PT(OOC)(2)C=C(CH3)(2) - LEE, YA; JUNG, OS; SOHN, YS; LEE, KB (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
New platinum(II) complexes of A(2)Pt(IPM) [A(2) = tetrahydro-4H-pyran-4,4-di(methylamine) (THPDMA), 2,2-dimethyl-1,3-propanediamine (DMPDA), trans-(+/-)-diaminocyclohexane (DACH); A = NH3, isopropylamine (IPA), cyclopropylamine (CPA);IPM = isopropylidenemalonate] have been synthesized and characterized by means of X-ray crystallography and various spectroscopies. The crystal structure of (THPDMA)Pt (IPM) . 5H(2)O was determined. The platinum atom adopts a typical square planar arrangement with two nitrogen atoms in the cis positions. The molecular structures are retained in aqueous solution at room temperature. However, the present complexes change to dimethyl sulphoxide (DMSO) adducts on standing for a long time or increasing temperature in DMSO: the monodentate amine complex produces (A) (DMSO)Pt(OOC)(2)C=C(CH3)(2), whereas the chelate amine analogue affords A(2)Pt(+) (DMSO)(OOC)C(COO-)=C(CH3)(2).
Keywords: COMPLEXES